Determination of the Decision Support System Based on Teacher Performance Rewards Receiver With AHP method on SMK Negeri 1 Beringin - Subowo, Subowo; Riandari, Fristi (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Abstract Teacher performance evaluation of SMK Negeri 1 Beringin Deli Serdang Regency was conducted on 3 teachers as samples of teacher performance appraisal data as material for consideration of the continued relationship of cooperation for the future budget. Components of performance appraisal of teacher performance at VOCATIONAL SCHOOL 1 Beringin Deli Serdang Regency are work performance, performance quantity, performance discipline, cooperation, and loyalty. Problems with the teacher performance appraisal process that occur due to unclear criteria and assessment weights. A method in a decision support system can help the optimal decision making process, the AHP method in determining the performance evaluation of honorary employees. There are three employee performance weights, which are very good, good, sufficient and good enough, from 3 employees who are categorized by performance appraisal, after applying the AHP method, it is obtained Irmala, S.Kom value = 1.139 Iswadi, S.Kom value = 0.739 and Hadi Suprayetno, ST value = 0.79, the three teachers were categorized with very good performance assessments.